Universal CAGE-WANT Questionnaire: “Think & Fill in the Suspect, Self-Assess and Screen! You May Need Help For, What You Have Filled In!” - Gupta, Deepak (Indian Journal of Community Health, 2014)
In 1970, John A. Ewing [1] developed CAGE questionnaire for identifying hidden alcoholism. It has been almost a half-century since 1970s [2] and CAGE questionnaire has expanded its promise and utility in identifying other addictions like for drug use as CAGE-AID in 1990s [3] and for personal electronic devices as University of Rochester Modified CAGE Questions in 2010s [4]. It seems the time is ripe to document a Universal CAGE Questionnaire (Table 1): Universal CAGE-WANT Questionnaire) wherein any and every subject of fascination and/or any and every human urge to WANT can be incorporated for self-assessment and/or screening to identify addiction for the suspected and tested WANT.